Non-Syndromic Solitary Neurofibroma in floor of the mouth: A case report - N, Balan; Mani M, Sudhaa; Ahamed S, Yasmeen; G.S, Sivaraman; V, Ezhilarasi (Indian Journal of Case Reports, 2019)
Neurofibromas are rare in the head and neck region, but most frequent tumor of neural origin. Oral hard and soft tissue is affected bythe tumor. In this paper, we describe an unusual case of non-syndromic solitary neurofibroma of the floor of the mouth in a 70-yearfemalepatient with a chief complaint of growth in the floor of the mouth for the past 3 months. An occlusal, intraoral periapicalradiograph and CT imaging were done. After confirming the diagnosis, the lesion was excised under local anesthesia and the specimenwas submitted for histopathological examination. On subsequent follow-up, the patient was asymptomatic. Intraoral neurofibromaalthough uncommon, deserve special attention because of their similarity with other inflammatory neoplastic condition, and theirtendency to undergo malignant transformation.